Analysis of the applied standards for assessing regressivity in economic, social, cultural, and environmental rights during economic crises - Witker Velásquez, Jorge Alberto; Vázquez May, Reyes Enrique (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
This article primarily aims to document and analyse the most relevant standards applied in resolving cases involving potential regressive measures and insufficient available resources during economic crises. For this purpose, it examines the assessments developed and utilised in judicial decisions by the constitutional courts of Spain, Portugal, Colombia, and Mexico, in contrast with those of International Human Rights Law, particularly within the Universal System and the European and Inter-American regional systems. This comparative analysis seeks to identify a test for regressive measures that addresses the common elements of Economic, Social, Cultural, and Environmental Rights (ESCER/ DESCA): their core content, basic obligations, and multidimensional scope.